Early occurrence of heart failure hospitalization or ventricular arrhythmia re‐define the long‐term prognosis after CRT - Anna Zsofia Toth; Laszlo Nagy; Krisztina Maria Szabo; Vivien Racz; Alexandra Kiss; Gabor Sandorfi; Attila Borbely; Tibor Laszlo Nagy; Zoltan Csanadi (ESC Heart Failure)
Abstract Aims Classifying patients as responders or non‐responders to cardiac resynchronization therapy (CRT) has been recently challenged, suggesting that preventing heart failure (HF) progression may also provide survival benefits. We assessed a novel classification based on echocardiographic left ventricular (LV) reverse remodelling and the occurrence of acute HF hospitalization (HHF) or sustained ventricular arrhythmia (VA) within 1‐year post‐CRT. Methods and results Patients implanted with a CRT defibrillator (CRT‐D) at our department between 2010 and 2020 were classified based on the change in LV ejection fraction (LVEF) within 1 year as responders (increase ≥ 10%), non‐progressors (increase <10%) or progressors (decline). Patients in each category were further divided based on the occurrence or absence of an HHF/VA event within 1‐year post‐implantation. Long‐term survival free of heart transplantation or LV assist device implantation was calculated for all six subgroups. Cohorts demonstrating no significant between‐group differences were grouped together and reclassified as improved, stabilized or worsened. One hundred nineteen responders, 79 non‐progressors and 69 progressors were identified based on the echocardiographic response. Long‐term event‐free survival was higher for responders as compared with non‐progressors (hazard ratio [HR] 0.51, P = 0.002) or progressors (HR 0.34, P < 0.0001). Furthermore, non‐progressors had better outcome than progressors (HR 0.63, P = 0.03). Long‐term prognosis in patients was superior with versus without an HHF/VA event within each group of responders (HR 0.47, P = 0.03), non‐progressors (HR 0.31, P = 0.0001) or progressors (HR 0.38, P = 0.0004). No survival difference was found between responders and non‐progressors with no event (HR 0.69, P = 0.09), who were recategorized as improved. Long‐term prognosis was also similar in responders with any event and in progressors with no event (HR 0.98, P = 0.88; stabilized), as well as in non‐progressors and progressors with any event (HR 0.87, P = 0.63; worsened). Median survival rates demonstrated significant differences between the improved, stabilized and worsened groups (102.3, 62.0 and 24.4 months; HR 0.53, P = 0.006 between improved and stabilized; HR 0.41, P < 0.0001 between stabilized and worsened; HR 0.21, P < 0.0001 between improved and worsened cohorts, respectively). Conclusions Long‐term survival can be predicted based on the change in LVEF and on the occurrence of an HHF/VA event within 1‐year after CRT‐D implantation. Stabilized patients have significantly better prognosis as compared with the worsened group. Patients with strikingly poor prognosis can be identified using this assessment method.